The Understanding of learner integration in a selected Ex-Model C school - Kanyopa, Theresia Joakim; Hlalele, Dipane Joseph (Penerbit Universiti Kebangsaan Malaysia, 2023)
Learner integration has become an asset for the meaningful resettlement of learners from different backgrounds in a one learning environment. Psychologically, the learner integration phenomenon is a crucial component in a teaching and learning context because it is linked to psycho-socio elements for the learners’ well-being. This study aimed to explore the understanding of learner integration in an Ex-Model C school. This paper identified the central elements of the diverse perceptions constituting successful learner integration in an Ex-Model C school. Moreover, the key traits in the understanding of learner integration were presented about the three overall themes that emerged from the findings of the study. The study was conceptualised within the Critical Emancipatory Research (CER) theoretical framework. The participants and research site were selected using purposive and convenience sampling. Data were generated through photovoice and multi-stakeholder meetings. Based on the South African historical background, this study maintains that learner integration has a transformative agenda as the phenomenon leans towards the democracy, social justice, and emancipation of education practices that are negatively affected by the inherent issues from the previous education system in South Africa. This implies that effective learner integration plays an essential part in ensuring equity, equality, and democracy in South African schools specifically Ex-Model C schools.